Republic of Kazakhstan : 2021 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Kazakhstan. (IMF Staff Country Reports; Country Report, 2022)
Activity returned to its pre-COVID level in 2021. Inflation remains well above the NBK's 4-6 percent target band, and spillovers from sanctions on Russia will exacerbate price pressures and weaken economic growth in 2022. Kazakhstan benefits from strong fiscal and external buffers but risks to the outlook are elevated due to the uncertain impact on Kazakhstan of the sanctions on Russia and heightened domestic tensions since the January social unrest episode. In the medium term, non-oil growth under the baseline is expected to converge to about 4 percent. Sustainable growth will require greater economic diversification. Climate-related challenges are acute for Kazakhstan given its outsized hydrocarbon sector, high per-capita greenhouse gas emissions, and low domestic energy prices.